2016
DOI: 10.1177/0969141316641149
|View full text |Cite
|
Sign up to set email alerts
|

Molecular picture of cobalamin C/D defects before and after newborn screening era

Abstract: Objective Birth prevalence of Cobalamin (Cbl) C or D defects in Portugal is an estimated 1:85,000, one of the highest worldwide. We compared the genotype/phenotype of patients identified with CblC or CblD before and after the implementation of expanded newborn screening. Methods Twenty-five Portuguese CblC/D patients, 14 symptomatic and 11 identified through screening, were diagnosed using gas chromatography or tandem mass spectrometry. Molecular characterization was performed through the study of MMACHC and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In this population, the cblC defect is the most frequent remethylation disorder. Since some European countries have recently introduced NBS, increasing numbers of identified patients can be expected …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this population, the cblC defect is the most frequent remethylation disorder. Since some European countries have recently introduced NBS, increasing numbers of identified patients can be expected …”
Section: Discussionmentioning
confidence: 99%
“…Since some European countries have recently introduced NBS, increasing numbers of identified patients can be expected. 18 For cblC disease, severe organ manifestations such as thromboembolic events, cardiac or small vessel involvement (e.g. atypical HUS, pulmonary hypertension) were T A B L E 3 Combinations of the four most frequently used treatment modalities betaine, OH-Cbl, folate/folinic acid and carnitine and dietary treatment in 161 patients with the cblC defect and on enrolment (dose ranges in Supplementary Table S6) White: No drugs as recommended in guidelines Grey: Drug with proven effect ± other drugs Dark grey: Drug with proven effect only rarer in this sample than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…These results question the sensitivity of newborn screening in identifying infants with cobalamin C disease, especially those with genotypes predicting mild disease. Nogueira et al 32 showed that since the implementation of expanded newborn screening in 2004 in Portugal, all individuals with cobalamin C disease identified were homozygous for the c.271dupA (p.Arg91LysfsX14) pathogenic variant. They hypothesized that this finding may be related to low birth prevalence of late onset forms or the challenges of identifying these infants through newborn screening.…”
Section: Discussionmentioning
confidence: 99%
“…Some common mutations are found in the MMACHC gene: c.271dupA (p.Arg91Lysfs*14), c.331C>T (p.Arg111Ter) and c.394C>T (p.Arg132Ter). [71,72] The p.Arg91Lysfs*14 and p.Arg111Ter mutations were associated with early-onset disease, while the p.Arg132Ter mutation is primarily associated with late-onset disease. [73,74] Wang et al (2010) reported that the c.609 G>A (p.W203X) mutation, which results in a premature termination codon at amino acid residue 203 located in the C-terminal region of MMACHC, was detected in 39 of 46 patients, or 85% of alleles, making this mutation the most frequent in Chinese cblC patients.…”
Section: Clinical Picturementioning
confidence: 99%